Cultural capital, creativity and sustainable development: current challenges on cultural production - Oliva Abarca, Jesús Eduardo (2016)
The basis of the relationship between culture and development could be located on the concept of cultural capital, which is defined as the reservoir of symbols, narratives, images, ideas and values that enables the existence of diverse cultural practices and expresions that are updated by human creativity. Despite the benefits, the idea of culture as development factor deals with many problems. The aim of this paper is to examine how is legitimated the discourse of culture as a resource for develpment, to analyze the relations between cultural capital, creativity and sustainable human development and, also, to indicate the challenges that cultural production faces nowadays.